PENGARUH KEPERCAYAAN ATAS SISTEM INFORMASI AKUNTANSI, PELATIHAN REWARD TERHADAP KINERJA KARYAWAN PADA KSP KOPDIT MEGU LEKUK HUBIN - Goreti Towe Punang, Maria; Mitan, Wilhelmina; Pati Sanga, Konstantinus (Accounting UNIPA - Jurnal Akuntansi, 2023)
This research aimed to (1) determine the effect of trust over accounting information systems, training, and reward on employe performance at Megu Lekuk Hubin Credit Union. This research method was quantitative. Data analysis using multiple linier regression analysis. The hypothesis test used was a simultaneous test (F test), partial test (t test), and test of the coefficient of determination (R2 test). The population in this research werw 30 employees of Megu Lekuk Hubin Credit Union. Due to the limited population, the research was carirried out through a census or saturated sampling. The results of this research indicate that the variables of employee performance, trust in accounting information systems,training,and rewards were categorized as very good. The t-test statistic result showed that partially the trust variable and training variable in the accounting information system had no effect on employee performance while the reward variable had an effect on employee performance. The statistical results of the F test showed that all independent variables simultaneously and significantly affect employee performance. Based on the determination analysis, the three independent variables in this research could adequately account for the three factors that significantly impact employee performance.